2013
DOI: 10.1111/1468-0106.12034
|View full text |Cite
|
Sign up to set email alerts
|

Tax Auditing as a Public Good Game: An Experimental Study on Punishment and Compliance

Abstract: Prior experimental studies on tax evasion generally assume that the budget and the probability of audit are exogenously given, and ignore taxpayers' incentives to detect evasion and their compliance behaviour under such incentives. The experimental evidence of the present paper shows that, on average, subjects are willing to spend 20 to 30% of their tax revenue on auditing. Compliance is also greatly improved if subjects can determine the budget and, hence, the probability of audit. These findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several findings in the tax compliance field have offered a similar result (Hsu & Kan, 2020;Rahmayanti et al, 2020;Oladele et al, 2019). However, it contradicts the findings of Bangun et al (2018) and Lavic (2023).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several findings in the tax compliance field have offered a similar result (Hsu & Kan, 2020;Rahmayanti et al, 2020;Oladele et al, 2019). However, it contradicts the findings of Bangun et al (2018) and Lavic (2023).…”
Section: Discussionmentioning
confidence: 81%
“…The effects of tax penalty on tax compliance have been widely examined (Nguyen et al, 2020;Rahmayanti et al, 2020;Widuri et al, 2019). Several studies have revealed that tax penalty is significantly related to taxpayers' compliance (Hsu & Kan, 2020;Rahmayanti et al, 2020;Widuri et al, 2019), while other studies have found no significant relationship (Bangun et al, 2018;Mahdi & Ardiati, 2017). However, this plethora of findings has mainly focused on taxpayers' general compliance and evasion.…”
Section: Tax Penaltymentioning
confidence: 99%
“…In an experimental study by Hsu (2013), it was found that on average, subjects are willing to spend 20% to 30% of their tax revenue on auditing. Compliance is also improved if subjects can determine the budget and the probability of audit.…”
Section: Tax Audit Outcomementioning
confidence: 99%